2017
DOI: 10.1097/01.ogx.0000524510.66825.09
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Antidepressant Use During the First Trimester of Pregnancy With Preterm Birth, Small for Gestational Age, Autism Spectrum Disorder, and Attention-Deficit/Hyperactivity Disorder in Offspring

Abstract: Importance-Prenatal antidepressant exposure has been associated with adverse outcomes. Previous studies, however, may not have adequately accounted for confounding. Objective-To evaluate alternative hypotheses for associations between first-trimester antidepressant exposure and birth and neurodevelopmental problems. Design, Setting, and Participants-This retrospective cohort study included Swedish offspring born between 1996 and 2012 and followed through 2013 or censored by death or emigration. Analyses contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 18 publications
3
63
0
1
Order By: Relevance
“…Evidence suggests women are reluctant to take medication in pregnancy, despite this we observed, across various drug classes, a substantial use of prescription drugs. Fetotoxicity is a great concern, also regarding some antidepressants and antiepileptic drugs, but untreated medical conditions are equally worrying and may harm the developing fetus . Any decision regarding medication use in pregnancy should therefore be personalized and based on the risk perceptions of the health care professional and the woman's preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests women are reluctant to take medication in pregnancy, despite this we observed, across various drug classes, a substantial use of prescription drugs. Fetotoxicity is a great concern, also regarding some antidepressants and antiepileptic drugs, but untreated medical conditions are equally worrying and may harm the developing fetus . Any decision regarding medication use in pregnancy should therefore be personalized and based on the risk perceptions of the health care professional and the woman's preferences.…”
Section: Discussionmentioning
confidence: 99%
“…A study on data from five Nordic countries by Furu and colleagues showed that their adjusted findings in a cohort study could not be repeated in a sibling analysis . A recently published study demonstrated that associations between exposure to ADs in early pregnancy and several birth and neurological disorders diminished in the adjusted models and in the sibling design analyses, which indicates confounding, especially confounding by indication, or other types of confounding in the study . Confounding by indication and confounding by background characteristics have been of concern in observational studies and researchers have been exploring different methods to adjust for those factors …”
Section: Discussionmentioning
confidence: 99%
“…To further examine the role of genetics and maternal mood, two recent population‐level studies have attempted to disentangle potential genetic and environmental mechanisms by using sophisticated statistical methods to adjust for possible measured and unmeasured confounding factors. In one study, using large population‐level data registries from Sweden, Sujan et al examined associations between first trimester antidepressant exposure, birth, and neurodevelopmental outcomes such as autism spectrum disorder and attention deficit‐hyperactivity disorder in over a million children, accounting for family, timing of exposure, and paternal factors (Sujan et al, ). In this study, first trimester maternal antidepressant use was associated with a small increased risk of preterm birth, but not with risk for adverse neurodevelopmental outcomes.…”
Section: Ssri Antidepressant Effectsmentioning
confidence: 99%
“…Importantly, maternal depression and autism may also be related through genetic mechanisms, thereby rendering SSRI exposure as a secondary risk factor underlying the effect of maternal mood (either by means of genetic inheritance or an environmental influence). Research has found a familial association between ASD and depression (Smalley et al, ), although not all associations are consistent (Sujan et al, ) or common (Brown et al, ).…”
Section: Ssri Antidepressant Effectsmentioning
confidence: 99%